Etiologies and Predictors of ST-Segment Elevation Myocardial Infarction - Bae, Myung Hwan; Cheon, Sang Soo; Song, Joon Hyuk; Jang, Se Yong; Choi, Won Suk; Kim, Kyun Hee; Park, Sun Hee; Lee, Jang Hoon; Yang, Dong Heon; Park, Hun Sik; Cho, Yongkeun; Chae, Shung Chull (Korean circulation journal, 2013)
Rapid diagnosis of ST-segment elevation myocardial infarction (STEMI) is essential for the appropriate management of patients. We investigated the prevalence, etiologies and predictors of false-positive diagnosis of STEMI and subsequent inappropriate catheterization laboratory activation in patients with presumptive diagnosis of STEMI. Four hundred fifty-five consecutive patients (62±13 years, 345 males) with presumptive diagnosis of STEMI between August 2008 and November 2010 were included. A false-positive diagnosis of STEMI was made in 34 patients (7.5%) with no indication of coronary artery lesion. Common causes for the false-positive diagnosis were coronary spasm in 10 patients, left ventricular hypertrophy in 5 patients, myocarditis in 4 patients, early repolarization in 3 patients, and previous myocardial infarction and stress-induced cardiomyopathy in 2 patients each. In multivariate logistic regression analysis, symptom-to-door time >12 hours {odds ratio (OR) 4.995, 95% confidence interval (CI) 1.384-18.030, p=0.014}, presenting symptom other than chest pain (OR 7.709, 95% CI 1.255-39.922, p=0.027), absence of Q wave (OR 9.082, CI 2.631-31.351, p<0.001) and absence of reciprocal changes on electrocardiography (ECG) (OR 17.987, CI 5.295-61.106, p<0.001) were independent predictors of false-positive diagnosis of STEMI. In patients whom STEMI was planned for primary coronary intervention, the false-positive diagnosis of STEMI was not rare. Correct interpretation of ECGs and consideration of ST-segment elevation in conditions other than STEMI may reduce inappropriate catheterization laboratory activation.